Th2 differentiation is necessary for soft tissue fibrosis and lymphatic dysfunction resulting from lymphedema. Issue 3 (27th November 2012) - Avraham, Tomer; Zampell, Jamie C.; Yan, Alan; Elhadad, Sonia; Weitman, Evan S.; Rockson, Stanley G.; Bromberg, Jacqueline; Mehrara, Babak J.
Abstract : Lymphedema is a dreaded complication of cancer treatment. However, despite the fact that > 5 million Americans are affected by this disorder, the development of effective treatments is limited by the fact that the pathology of lymphedema remains unknown. The purpose of these studies was to determine the role of inflammatory responses in lymphedema pathology. Using mouse models of lymphedema, as well as clinical lymphedema specimens, we show that lymphatic stasis results in a CD4 + T‐cell inflammation and T‐helper 2 (Th2) differentiation. Using mice deficient in T cells or CD4 + cells, we show that this inflammatory response is necessary for the pathological changes of lymphedema, including fibrosis, adipose deposition, and lymphatic dysfunction. Further, we show that inhibition of Th2 differentiation using interleukin‐4 (IL‐4) or IL‐13 blockade prevents initiation and progression of lymphedema by decreasing tissue fibrosis and significantly improving lymphatic function, independent of lymphangiogenic growth factors. We show that CD4 + inflammation is a critical regulator of tissue fibrosis and lymphatic dysfunction in lymphedema and that inhibition of Th2 differentiation markedly improves lymphatic function independent of lymphangiogenic cytokine expression. Notably, preventing and/or reversing the development of pathological tissue changes that occur in lymphedema may be a viable treatment strategy for this disorder.—Avraham, T., Zampell, J. C., Yan, A., Elhadad, S., Weitman, E. S., Rockson, S. G., Bromberg, J., Mehrara, B. J. Th2 differentiation is necessary for soft tissue fibrosis and lymphatic dysfunction resulting from lymphedema. FASEB J. 27, 1114–1126 (2013). www.fasebj.org